Characterization of By-products with High Fat Content Derived from the Production of Bovine Gelatin [version 2; peer review: 2 approved] - Laura Botero; Liliana Maria Lellesch; Diego Fernando Roa-Acosta; Lina Marcela Agudelo Laverde; Victor Alonso Garcia Londoño; Natalia Marín González (F1000Research, 2023)
Background: Gelatin is a protein obtained by partial hydrolysis of collagen contained in skins, connective tissue and/or animal bones, which are by-products of the meat industry. The main raw material to produce bovine gelatin is the dermis of the skin, but there is a variation in fat and moisture content depending on the bovine skin origin. As a contribution to the circular economy and sustainability, these by-products with high fat content and the fat released from them during the gelatin production process can be managed for food industries, mainly in the development or formulation of animal feed. Methods: For the initial physicochemical characterization, moisture, fat, protein and ashes content were determined. Once the by-products with high fat content were identified, alteration parameters such as acidity, peroxide and saponification indexes were evaluated. Additionally, thermal, rheological and fatty acid composition characterization was carried out in order to study the possible applications of the by-products. Results and Discussion: The results showed that certain by-products have a fat content of less than 15%, so the viability of their use is limited. On the other hand, some by-products have a fat content exceeding 30%; however, their extraction can only be done manually, resulting in a low efficiency process. By-products removed from the supernatant in the extractors presented fat percentages of 99.9 and 98.9%, and there exists the possibility of implementing a mechanical method for their extraction. The analysis of alteration and oxidation parameters, thermal and rheological characterization, fatty acid profile and solid fat content were exclusively conducted on these high-fat content by-products. Based on the characterization, these by-products could be valued and incorporated into animal feed formulations. Nevertheless, certain limitations exist for their use in applications such as biodiesel production or the food industry.